Astrophysical Calibration of the Oscillator Strengths of Yj-Band Absorption Lines in Classical Cepheids - Saez-Elgueta, S (Oxford University Press, 2024)
Newly-developed spectrographs with increased resolving powers, particularly those covering the near-IR range, allow the characterization of more and more absorption lines in stellar spectra. This includes the identification and confirmation of absorption lines and the calibration of oscillator strengths. In this study, we provide empirical values of loggf based on the abundances of classical Cepheids obtained with optical spectra to establish the consistency between optical and infrared abundance results. Using time series spectra of classical Cepheids obtained with WINERED spectrograph (0.97-1.35 μm, R∼ 28000), we demonstrate that we can determine the stellar parameters of the observed Cepheids, including effective temperature (Teff), surface gravity (logg), microturbulence (ξ), and metallicity ([M/H]). With the newly calibrated relations of line-depth ratios, we can achieve accuracy and precision comparable to optical studies, with uncertainties of ∼90 K and 0.108 dex for Teff, and logg, respectively. Finally, we created a new atlas of absorption lines, featuring precise abundance measurements of various elements found in the atmosphere of Cepheids, including neutron-capture elements whose loggf values have been astrophysically calibrated. © 2024 The Author(s).